Relaxation processes in nonstoichiometric YBa₂Cu₃O₇-δ single crystals during annealing and at high pressure - Obolenskii, M.A.; Vovk, R.V.; Bondarenko, A.V. (Functional Materials, 2005)
The critical temperature relaxation processes and resistivity for YBa₂Cu₃O₇-δ single crystals with oxygen deficit δ ≤ 0,5 during annealing at room temperature and in case of high hydrostatic pressure up to 7 kbar have been studied. It is shown that Тс(δ) dependence evolution during annealing is in satisfactory agreement with the existing theoretic models. When the samples with oxygen deficit δ ≤ 0,5 are kept under pressure at room temperature, the carriers number for low-temperature phase reduces, while the opposite process of holes number increase takes place in the high-temperature phase. The authors have determined the activation energy and characteristic times for relaxation processes for isobaric and isothermal exposure of the studied samples.